Sistem Informasi Logistik PT. Atri Distribusindo Banda Aceh - Heranti; Ahmad, Lukman; Ihsanuddin (Computer Journal, 2024)
The utilization of information technology at PT. Atri Distribusindo Banda Aceh is still limited, particularly in logistics management, which is conducted manually. This situation complicates administrative processes, leading to delays and a high risk of errors in inventory management. To address these issues, this study develops a computerized logistics information system using the prototyping method, PHP, and MySQL. The prototyping approach allows for iterative feedback during system development, ensuring the system meets operational needs more effectively. The system is designed to enhance data accuracy and improve workflow efficiency in logistics operations. Based on observations and analysis, the logistics information system is expected to provide accurate and timely information, ultimately supporting better decision-making within PT. Atri Distribusindo Banda Aceh.